2023
DOI: 10.1007/s10238-023-01116-y
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the clinical characteristics of influenza-COVID-19 co-infection

Abstract: COVID-19 has impacted populations across the globe and has been a major cause of morbidity and mortality. Influenza is another potentially deadly respiratory infection that affects people worldwide. While both of these infections pose major health threats, little is currently understood regarding the clinical aspects of influenza and COVID-19 co-infection. Our objective was to therefore provide a systematic review of the clinical characteristics, treatments, and outcomes for patients who are co-infected with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…Our study observed a significant increase in RSV and IAV coinfection rate in 2023 is worth concerning. Coinfection of COVID‐19 and influenza has been shown to result in more severe clinical outcomes, such as mortality, mechanical ventilation, and ICU admission 35 . Research conducted in Brazil revealed higher fatality rates in cases of concurrent infections involving the Omicron and influenza A (H3N2) compared to single infections 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study observed a significant increase in RSV and IAV coinfection rate in 2023 is worth concerning. Coinfection of COVID‐19 and influenza has been shown to result in more severe clinical outcomes, such as mortality, mechanical ventilation, and ICU admission 35 . Research conducted in Brazil revealed higher fatality rates in cases of concurrent infections involving the Omicron and influenza A (H3N2) compared to single infections 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Cough was another common symptom in COVID-19 patients ( 11 , 16 , 25 27 ). The incidence of cough (71.6%) in our study was similar to that reported in other studies ( 11 , 26 , 27 ), but higher than the data from a systematic review of COVID-19 (25.4%) ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] In addition, co-infection in the community can readily occur due to crowding, lapses in hand hygiene, or other shared epidemiologic risk factors. 6 We recognize that the early months of the COVID pandemic might have suggested a spurious potential negative correlation between some pathogens because COVID increased in the spring whereas influenza typically increases in autumn.…”
mentioning
confidence: 92%